Knowledge and awareness of the cause, prevention and control of cervical cancer amongst female undergraduates and faculty of health sciences: a cross sectional survey - Tandon, Abhishek; Raja, Snigdha; Pai, Mangala M.; Unnikrishnan, B.; Kanchan, Tanuj (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Carcinoma cervix is the second most common cancer in women worldwide, and the most common in India. In this study, the current knowledge of female undergraduates and faculty of health sciences regarding the various parameters like risk factors, symptoms, screening tests and vaccinations pertaining to cervical cancer was assessed. Methods: A cross-sectional, self-administered anonymous questionnaire-based survey was carried out, in a medical college in Mangalore, which included 260 staff and students. Non random sampling was done and the study was carried out only after gaining institutional Ethical community approval and written informed consent from the subjects. Results: Majority of the participants 185 (71.4%) were aware that cervical cancer is one of the most wide- spread gynecological cancers in Asia. The awareness of causative agents of cervical cancer was known to 53.9% of the undergraduates and 50% of the faculty members. 73% of the total study groups have heard of HPV and around 68% agreed that it was detectable. 71% of the study sample had heard about the Pap smear test and 42% have undergone the test. The questions pertaining to the preventive measures of cervical cancer had good faculty preponderance with 91.8% giving a positive response. 84.1% of the students and 79.5% of the faculty members knew that abnormal vaginal bleeding was a symptom. Conclusions: In this study an attempt has been made to study the correlates of knowledge of cervical cancer in a cohort which consisted of health care undergraduate and faculty. Majority of our study group was well aware of the various risk factors of cervical cancer and its preventable nature however awareness regarding the association between diets, multiple pregnancies and use of tobacco was poor.